Violence Against Women During Coronavirus When Staying Home Isn't Safe - Pfitzner, Naomi; Fitz-Gibbon, Kate; Walklate, Sandra; Meyer, Silke; Segrave, Marie (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This open access book brings together leading international violence researchers to examine the impact of the coronavirus pandemic on experiences of, and responses to, domestic and family violence. Drawing on empirical work situated within an international context, this book presents evidence alongside country specific case studies to provide a global exploration of how women's insecurity increased during this global health crisis at the same as their access to support services reduced. In addition, the differential impacts of the pandemic in relation to the experiences of priority cohorts, including violence experienced by children and temporary migrant women is also explored. The key focus is on the nature, extent, and responses to the COVID-19 pandemic on service delivery, accessibility of support, and access to justice for women experiencing domestic and family violence. Naomi Pfitzner is Lead Researcher with the MonashGender and Family Violence Prevention Centre and Lecturer in Criminology in the Faculty of Arts, Monash University, Australia. Kate Fitz-Gibbon is Director of the Monash Gender and Family Violence Prevention Centre and Professor of Social Sciences in the Faculty of Arts, Monash University, Australia. Sandra Walklate is Eleanor Rathbone Chair of Sociology at the University of Liverpool, UK, Professor of Criminology at Monash University, Australia, and an Adjunct Professor at QUT, Australia. Silke Meyer is the Leneen Forde Chair in Child & Family Research at Griffith University and an Adjunct Professor at the Monash Gender and Family Violence Prevention Center at Monash University, Australia. Marie Segrave is an ARC Future Fellow and a Professor of Criminology in the Faculty of Arts, Monash University, Australia. .